The Impact of Artificial Intelligence on the Environment from the Perspective of Iraqi Criminal Law - Ahmed, Yousif (Journal of Legal Sciences, 2025)
Artificial intelligence has a two-fold impact on the environment in which humans live. It is positive in preserving the environment by repelling the dangers of machines and technology, on the one hand, and negative in its impact on humans through radioactive emissions, gases, and machines used by these technologically advanced devices locally and internationally and the extent of their impact on humans.Through this research, we will discuss the Iraqi legislation that dealt with the protection and improvement of the environment and its preservation from dangers, including the Iraqi Penal Code No. 111 of 1969 as amended, the Environmental Protection and Improvement Law No. 76 of 1986, the Environmental Protection and Improvement Law No. 3 of 1997, the Environmental Protection and Improvement Law in the Kurdistan Region No. 8 of 2008, the Environmental Protection and Improvement Law No. 27 of 2009 in force, the Ministry of Environment Law No. 37 of 2008, and Instructions No. 1 of 2013 issued by the Iraqi Ministry of Environment, and the extent of the positive and negative impact of artificial intelligence on the environment and when criminal liability is established.